Epidemiology of acute coronary heart disease in the Russian Federation: experience and perspectives - S. S. Yakushin; N. N. Nikulina (Кардиоваскулярная терапия и профилактика)
This article aims to focus the attention of various health professionals, in particular practitioners and decision  makers, on the problem of quality of statistical information on acute coronary heart disease (CHD) morbidity and  mortality in the Russian Federation (RF). The authors summarize relevant evidence from local and international  studies. The current system of national epidemiology statistics in the RF is analysed. Potential ways to improve the  data collection mechanisms for acute CHD are discussed. In particular, the international expert consensus on  acute CHD terminology and diagnostics in epidemiological and clinical studies is presented, which could harmonize relevant research if implemented locally.